THE ROLE OF PRAGMATIC EFFECT OF PLAY OF WORDS IN THE TEXT OF ANIMATION SERIES AS A SPECIFIC SPEECH GENRE - Natalia Kabylkina (Гуманитарные и юридические исследования)
The article deals with the role of pragmatic effect of play of words in the text of the animation series as a speciic speech genre. Animation, as ilm for children and film designed for all family, has not only entertaining, but also educational function, which actualizes the study of pragmatic effect in our research. Play of words in the modern communicative practice is applied in the didactic purposes as a subconscious form of impact on the recipient, for the purpose of the transfer of the author's assessment. Question of transfer of effects inherent in play on words from one language to another is a problem now. This problem is connected not only with language, but also with cultural distinctions. The globalization processes happening at the present stage make essential changes not only to life of society, but also to language. The author conirms the theoretical and methodological basis of pragmatic effect of play on words in the text of the animation series on the basis of the American animation. The author examines the functions of play of words, which are determined by the author's intention and expressed a special text organization for creating pragmatic effect.